Hall probe calibration in high-precision magnetic field mapping system of superconducting cyclotron - Xu Manman; Cao Chuqing; Fu Yili; Wu Yonghong; Wang Xiangdong; Su Yongsheng; Xi Lin; Liu Yongming (Nukleonika)
Superconducting cyclotron can generate high-energy proton beams and are mainly used for radiation therapy of tumors and cancers. In the superconducting cyclotron SC200, the maximum magnetic induction intensity can typically reach up to 4.6 T, and the magnetic field accuracy is 1e-4. Hall probes are commonly used tools for measuring high-intensity magnetic fields.